Prophylactic AEDs Treatment for Patients With Supratentorial Meningioma Does Not Reduce the Rate of Perioperative Seizures: A Retrospective Single-Center Cohort Study - Yang, Ming; Cheng, Yong-Ran; Zhou, Meng-Yun; Wang, Ming-Wei; Ye, Lan; Xu, Zu-Cai; Feng, Zhan-Hui; Ma, Xun-Tai (Frontiers in Oncology, 2020)
Meningiomas, the most common brain tumor, inevitably require surgical treatment. However, the efficacy of prophylactic antiepileptic drugs (AEDs), in reducing the frequency of new-onset seizures during the perioperative period remains controversial. To further clarify if prophylactic antiepileptic drug treatment for patients with meningioma had value, we reviewed the medical records of 186 supratentorial meningioma patients who were operated at our hospital between 2016 and 2018. SPSS 24.0 software was used for statistical analysis. The results of univariate analysis showed that factors including age, sex, the course of the disease (years), maximum cross-sectional area of the tumor, location of the tumor, multiple or single tumors, adjacent to the cortex, peritumoral brain edema, World Health Organization classification, and peritumoral adhesion were not associated with perioperative seizures (P > 0.05). Furthermore, the results of multivariate analysis revealed abundant blood supply (OR 1.78 P=0.01), hydrocephalus (OR 5.67 P=0.04), and non-skull base location (OR 1.98 P=0.03) were significant risk factors for perioperative in-hospital seizures. Prophylactic valproic acid treatment did not contribute to the alleviation of perioperative seizures (OR 1.64 P=0.04). However, Multivariate logistic regression analyses excluding the patients with seizures before operation confirmed prophylactic valproic acid treatment did not reduce the frequency of seizures during the perioperative period (OR 1.58 P=0.05). Taken together, the data suggest that prophylactic valproic acid treatment for patients with supratentorial meningioma does not reduce the rate of perioperative seizures.